The potential to attract the interest of local and foreign tourism potential of Nagori Parik (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2019)
Toba Lake. Six other districts covered by the Lake Toba region are Toba Samosir Regency, North Tapanuli Regency, Humbang 2 Hasundutan Regency, Samosir Regency, and Dairi Regency. Subdistricts in Simalungun District included in the Lake Toba area are Pematang Silimakuta Subdistrict, Silimakuta Subdistrict, Haranggaol Horison Subdistrict, Dolok Pardamean Subdistrict, Pematang Sidamanik Subdistrict, and Girsang Sipangan Bolon Subdistrict (Republic of Indonesia, no year). Based on the data contained in the Simalungun Regency Government Performance Report 2016 (Republic of Indonesia, 2016), Lake Toba is one of the leading tourist attractions in Simalungun Regency. Some of the efforts that have been made to develop the tourism area are establishing cooperation with stakeholders in the tourism sector and holding the Lake Toba Party. As the largest cadera lake in the world, Lake Toba has the potential to attract both local and foreign potentials. However, the total tourist arrivals in Simalungun Regency in 2016 were 314,890 people consisting of 305,832 archipelago tourists and 9,058 foreign tourists